The Incorporation of Digital Citizenship Competency in e-Learning Materials for Junior High School Students: A Content Analysis - Kamaliya, Vikasari; Mayuni, Ilza; Palupi, Tara Mustikaning (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2023)
This study aims at investigating the way Digital Citizenship Competencies (DCC) are incorporated into digital learning materials (DLM) in a web-based learning platform called myenglishstep.com. By compiling 115 DLM of 7th up to 9th Grade and utilizing the content analysis method, the finding shows skills dimension is found to be the highest incorporation, followed by the knowledge dimension. In contrast, the attitudes and values dimension showed low occurrences compared to the previous dimension. Knowledge, skills, and attitudes dimensions of DCC are mostly incorporated in all DLM categories through tasks, contents, and visuals, while values dimensions are incorporated through contents for the most part and tasks. Therefore, these findings are expected to raise people's awareness of digital citizenship competencies and aid teachers and stakeholders in providing reliable and varied digital learning materials.